Identification of residues involved in nucleotidyltransferase activity of JHP933 from helicobacter pyloriby site-directed mutagenesis - Ye, Xianren; Zhao, Yanhe; Wu, Xiuling; Su, Yintao; Wu, Yunkun; She, Feifei (Archives of Biological Sciences, 2016)
Helicobacter pylori is a well-known bacterial pathogen involved in the development of peptic ulcer, gastric adenocarcinoma and other forms of gastric cancer. Evidence has suggested that certain strain-specific genes in the plasticity region may play key roles in the pathogenesis of H. pylori-associated gastroduodenal diseases. Therefore there is considerable interest in the strain-specific genes located in the plasticity regions of H. pylori. JHP933 is encoded by the gene in the plasticity region of H. pylori strain J99. Recently, the crystal structure of JHP933 has confirmed it as a nucleotidyltransferase (NTase) superfamily protein and a putative active site has been proposed. However, no evidence from direct functional assay has been presented to confirm the active site and little is known about the functional mechanism of JHP933. Here, through superimposition with Cid1/NTP complex structures, we modelled the complex structures of JHP933 with different NTPs. Based on the models and using rational site-directed mutagenesis combined with enzymatic activity assays, we confirm the active site and identify several residues important for the nucleotidyl transferring function of JHP933. Furthermore, mutations of these active site residues result in the abolishment of the nucleotidyltransferase activity of JHP933. This work provides preliminary insight into the molecular mechanism underlying the pathophysiological role in H. pylori infection of JHP933 as a novel NTase superfamily protein.